2018
DOI: 10.1016/j.ejrad.2018.02.028
|View full text |Cite
|
Sign up to set email alerts
|

Combined hyperpolarized 13C-pyruvate MRS and 18F-FDG PET (hyperPET) estimates of glycolysis in canine cancer patients

Abstract: A B S T R A C TF-FDG uptake were tested within groups. Between groups, the same measures were tested for group differences.Results: The main cancer types of the 17 patients were sarcoma (n = 11), carcinoma (n = 5) and mastocytoma (n = 1). Significant correlations between pyruvate-to-lactate rate constants and 18 F-FDG uptake were found for sarcoma patients, whereas no significant correlations appeared for carcinoma patients. The sarcoma patients showed a non-significant trend towards lower 18 F-FDG uptake and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 31 publications
(77 reference statements)
2
16
0
Order By: Relevance
“…In another study, on canine tumors, in which [ 18 F]FDG-PET and pyruvate-to-lactate exchange were combined across animals, neither SUV nor k pl values could differentiate between carcinomas and sarcomas, although the ratio of k pl over SUV mean was significantly higher in sarcomas than in the carcinomas, which was taken as indicating a difference in contribution of the Warburg effect to energy metabolism in these tumors. 59 The k pl /SUV ratio in our study was significantly higher in the LNCaP compared with the PC3 tumors.…”
Section: Discussionsupporting
confidence: 38%
See 2 more Smart Citations
“…In another study, on canine tumors, in which [ 18 F]FDG-PET and pyruvate-to-lactate exchange were combined across animals, neither SUV nor k pl values could differentiate between carcinomas and sarcomas, although the ratio of k pl over SUV mean was significantly higher in sarcomas than in the carcinomas, which was taken as indicating a difference in contribution of the Warburg effect to energy metabolism in these tumors. 59 The k pl /SUV ratio in our study was significantly higher in the LNCaP compared with the PC3 tumors.…”
Section: Discussionsupporting
confidence: 38%
“…A study in dogs showed a positive correlation between the label exchange rate between pyruvate and lactate and [ 18 F]FDG uptake in sarcoma lesions, but not in carcinomas. 58,59 In a subcutaneous hepatocellular carcinoma model, no correlation of pyruvate and lactate parameters with physiologic or histologic parameters was found. 62 Studies comparing [ 18 F] FDG-PET and [1-13 C]pyruvate MR measurements before and after treatment showed an earlier decline in pyruvate to lactate exchange rate compared with decline in [ 18 F]FDG uptake.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Access to such patients supports multiparametric imaging studies in a tractable period of time within their clinical management. Other examples of novel tracer development and application by inclusion of companion species include 13-C pyruvate magnetic resonance spectroscopy (21), and 18 F-tetrafluoroborate ( 18 F-BF − 4 or 18 F-TFB) for expressed sodium-iodide symporter (NIS) PET imaging (Figure 4), which could be a useful tool for clinical thyroid and neuroendocrine tumor imaging, for preclinical imaging of NIS-expressing disease models and for cell trafficking studies (22)(23)(24). We have also explored the utility of an 18 F-radiolabeled fatty acid 18 F-fluoro-thia-heptadecandoic acid for metabolic imaging of fatty acid oxidation, which is an emerging field in the study of cancer metabolism (Figure 5) (25,26).…”
Section: Novel Radionuclide Tracer Developmentmentioning
confidence: 99%
“…So far, only a few sites worldwide attempted to assess the flux of glucose through the glycolytic pathway either sequentially or simultaneously with FDG-PET and pyruvate imaging (HyperPET 25 - 28 ). Witney et al .…”
Section: Introductionmentioning
confidence: 99%